THE EFFECT OF THE USE OF ARROWUT STARCH AND SATURATED LEAF EXTRACT ON THE PHYSICOCHEMICAL AND ORGANOLEPTIC PROPERTIES OF ICE CREAM - Yastari Mufidah Rijanti; Kejora Handarini; Fadjar Kurnia Hartati; Erna Nursiyah Tanoyo (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
sweet taste , soft texture, and refreshing cold sensation. This study aims to examine the effect of variations in the concentration of arrowroot starch and katuk leaf extract on the physicochemical and organoleptic properties of ice cream. The study used a quantitative experimental method with a one-factor Completely Randomized Design (CRD), consisting of four treatments: P1 (22.5 % : 2.5%), P2 (20%: 5%), P3 (17.5%: 7.5%), and P4 (15%: 10%), each repeated three times. Ice cream making includes preparation of ingredients, boiling, mixing thickener, cooling, stirring, and freezing. Observed variables include melting speed, overrun, protein content , fat, total solids, polyphenols, as well as organoleptic tests of color, aroma, taste, and texture. Data analysis was carried out using ANSIRA, significant difference test (LSD/LSD/Duncan), Kruskal-Wallis test for organoleptic, and effectiveness test to determine the best treatment. The results showed that variations in the concentration of arrowroot starch and katuk leaf extract had a significant effect (p < 0.05) on the melting speed, polyphenol, protein, fat, and total solids levels, but did not have a significant effect (p > 0.05) on the overrun and texture values. Organoleptic tests showed that all treatments were in the neutral category. The best treatment was P4 (15% arrowroot starch: 10% katuk leaf extract) with the highest yield value (NH) of 0.86, melting speed of 1.30 g/minute, protein 4.53%, fat 2.08%, total solids 33.89%, polyphenols 2.27%, and color 3.30, aroma 3.76, taste 3.40, and texture 3.58 (neutral). This study shows that the combination of arrowroot starch and katuk leaf extract can produce functional ice cream with high nutritional value and sensory quality acceptable to consumers.